The effects of Ramadan intermittent fasting on sleep-wake behaviour and daytime sleepiness in team sport referees - Trabelsi, K.; Masmoudi, L.; Ammar, A.; Boukhris, O.; Khacharem, A.; Jemal, M.; Zlitni, S.; Bragazzi, N. L.; Clark, C. C. T.; Lastella, M.; Chtourou, H. (Journal of Sports Sciences, 2021)
The aim of the present study was to evaluate the impact of Ramadan fasting on sleep quality and daytime sleepiness in team sport referees. Seventy-eight male amateur team sport referees (age: 31.1 ± 10.8 years) participated in this study. Participants responded to the Arabic version of the Pittsburgh Sleep Quality Index (PSQI) and the Epworth sleepiness scale (ESS) questionnaires before (10-days prior) and during (last 7-days) the month of Ramadan.